Respuesta :
Answer: 3x + 13
Step-by-step explanation:
[tex]f(x)=3x^2+x\\f(a)=3a^2+a\\f(4)=3*4^2+4=52\\\\f(x)-f(4)=3x^2+x-52=(x-4)(3x+13)\\\\\dfrac{f(x)-f(4)}{x-4} =\dfrac{3x^2+x-52}{x-4} \\\\if\ x \neq 4\ then \\\\\dfrac{f(x)-f(4)}{x-4} =\dfrac{(x-4)(3x+13)}{x-4} \\\\=3x+13\\[/tex]
If [tex]f(x)=3x^2+x[/tex], then
[tex]f(4) = 3\cdot4^2+4 = 52[/tex]
so that the difference quotient is
[tex]\dfrac{f(x)-f(a)}{x-a} = \dfrac{3x^2+x-52}{x-4}[/tex]
Factorize the numerator:
[tex]3x^2+x-52 = (3x+13)(x-4)[/tex]
Then for x ≠ 4, we have
[tex]\dfrac{f(x)-f(a)}{x-a} = \dfrac{(3x+13)(x-4)}{x-4} = 3x+13[/tex]